1999
DOI: 10.1016/s1010-7940(99)00291-2
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins in cardiosurgery patients

Abstract: HSP72 is implicated in cardioprotection in combination with some other factors, and its pre-operational level, among other parameters, might be of prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…[7][8][9] However, there are few reports on circulating HSPs in human diseases. [23][24][25] The early peak of inducible HSP70 in plasma after CABG as demonstrated in our study is striking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] However, there are few reports on circulating HSPs in human diseases. [23][24][25] The early peak of inducible HSP70 in plasma after CABG as demonstrated in our study is striking.…”
Section: Discussionmentioning
confidence: 99%
“…7 Myocardial ischemia induces HSP70 as a stress response, 7 and HSP70 is increased in atrial tissue of patients with unstable angina. 8 Demidov and coworkers 9 found induction of HSP70 in myocardial cells in 40% of 33 patients undergoing CABG. Circulating inducible HSP70 after CABG has, to our knowledge, not been demonstrated previously.…”
mentioning
confidence: 99%
“…However, HSPs function not only within the cell to chaperone proteins and protect tissues from stress and injury but also extracellularly to signal cell stress or trauma (4). HSP70 is released into the circulation after coronary artery bypass grafting (11) and acute myocardial infarction (9), and extracellular HSP70 has been shown to induce cytokine production in cultured mononuclear cells (2).Although several studies (8,17,29,35) have examined the expression of HSC70 in the myocardium during ischemiareperfusion, it is unknown whether the myocardium releases HSC70 during ischemia-reperfusion. Nor is it known whether extracellular HSC70 has any effect on the cellular or tissue…”
mentioning
confidence: 99%
“…Although several studies (8,17,29,35) have examined the expression of HSC70 in the myocardium during ischemiareperfusion, it is unknown whether the myocardium releases HSC70 during ischemia-reperfusion. Nor is it known whether extracellular HSC70 has any effect on the cellular or tissue inflammatory response.…”
mentioning
confidence: 99%
“…The 70-kDa family of HSP (HSP70), in particular, plays a vital role in cellular protection and has been detected in various tissues subject to stress. 7,8 HSP70 expression was demonstrated in cardiovascular surgery patients, 9,10 and current experimental studies have demonstrated the efficacy of HSP70 induction before stress in reducing myocardial damage after ischemia-reperfusion. 11,12 However, this novel approach through the self-protective system has not yet been applied to CPB-induced inflammatory response.…”
mentioning
confidence: 99%